Socio-economic and demographic predictors of unmet need for contraception among young women in sub-Saharan Africa: evidence from cross-sectional surveys - Bright Opoku Ahinkorah; Edward Kwabena Ameyaw; Abdul-Aziz Seidu (BMC, 2020)
Abstract Introduction Globally, sub-Saharan Africa (SSA) bears the highest proportion of women with unmet need for contraception as nearly 25% of women of reproductive age in the sub-region have unmet need for contraception. Unmet need for contraception is predominant among young women. We examined the association between socio-economic and demographic factors and unmet need for contraception among young women in SSA. Methods Data for this study obtained from current Demographic and Health Surveys (DHS) conducted between January 1, 2010 and December 31, 2018 in 30 sub-Saharan African countries. The sample size consisted of young women (aged 15-24), who were either married or cohabiting and had complete cases on all the variables of interest (N = 59,864). Both bivariate and multivariable binary logistic regression analyses were performed using STATA version 14.0. Results The overall prevalence of unmet need for contraception among young women was 26.90% [95% CI: 23.82-29.921], ranging from 11.30% [95% CI: 5.1-17.49] in Zimbabwe to 46.7% [95% CI: 36.92-56.48] in Comoros. Results on socio-economic status and unmet need for contraception showed that young women who had primary [aOR = 1.18; CI = 1.12-1.25, p < 0.001] and secondary/higher levels of formal education [aOR = 1.27; CI = 1.20-1.35, p < 0.001] had higher odds of unmet need for contraception compared to those with no formal education. With wealth status, young women in the richest wealth quintile had lower odds of unmet need for contraception compared with those in the poorest wealth quintile [aOR = 0.89; CI = 0.81-0.97, p < 0.01]. With the demographic factors, the odds of unmet need for contraception was lower among young women aged 20-24 [aOR = 0.74; CI = 0.70-0.77, p < 0.001], compared with 15-19 aged young women. Also, young women who were cohabiting had higher odds of unmet need for contraception compared to those who were married [aOR = 1.35; CI = 1.28-1.43, p < 0.001]. Conclusion Our study has demonstrated that unmet need for contraception is relatively high among young women in SSA and this is associated with socio-economic status. Age, marital status, parity, occupation, sex of household head, and access to mass media (newspaper) are also associated with unmet need for contraception. It is therefore, prudent that organisations such as UNICEF and UNFPA and the Bill & Melinda Gates Foundation who have implemented policies and programmes on contraception meant towards reducing unmet need for contraception among women take these factors into consideration when designing interventions in sub-Saharan African countries to address the problem of high unmet need for contraception among young women.